2017
DOI: 10.7554/elife.28563
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl dihydroxylation of unassembled uS12/Rps23 regulates fungal hypoxic adaptation

Abstract: The prolyl-3,4-dihydroxylase Ofd1 and nuclear import adaptor Nro1 regulate the hypoxic response in fission yeast by controlling activity of the sterol regulatory element-binding protein transcription factor Sre1. Here, we identify an extra-ribosomal function for uS12/Rps23 central to this regulatory system. Nro1 binds Rps23, and Ofd1 dihydroxylates Rps23 P62 in complex with Nro1. Concurrently, Nro1 imports Rps23 into the nucleus for assembly into 40S ribosomes. Low oxygen inhibits Ofd1 hydroxylase activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Since casein kinase 1 family member Hhp2 accelerates Sre1N degradation, our results suggested that Ssp2/Gsk3/Gsk31 might act as inhibitors of Hhp2, or alternatively act on Sre1N activity independently of Hhp2. Previous studies suggested that Sre1 cleavage, Sre1N stability and Sre1N DNA binding are involved in the regulation of Sre1 activity [30][31][32]. Based on our present results, we propose that Ssp2 and Gsk3/Gsk31 might affect Sre1N stability to regulate Sre1 activity.…”
Section: Discussionsupporting
confidence: 76%
“…Since casein kinase 1 family member Hhp2 accelerates Sre1N degradation, our results suggested that Ssp2/Gsk3/Gsk31 might act as inhibitors of Hhp2, or alternatively act on Sre1N activity independently of Hhp2. Previous studies suggested that Sre1 cleavage, Sre1N stability and Sre1N DNA binding are involved in the regulation of Sre1 activity [30][31][32]. Based on our present results, we propose that Ssp2 and Gsk3/Gsk31 might affect Sre1N stability to regulate Sre1 activity.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast to ZmAKR4C9 , ZmRPS23 belongs to the ribosomal protein S12/S23 family that functions in translation fidelity [103]. Interestingly, several studies identified RPS23 as an enzyme substrate for the oxygenase OFD1 in fission yeast [104]. When little oxygen is around, OFD1 cannot hydroxylate RPS23.…”
Section: Discussionmentioning
confidence: 99%
“…Both low oxygen and physiological CO 2 promote the stability of Ume6, allowing filamentation to proceed (84). PHD-mediated regulation of the sterol regulatory element binding protein (SREBP)-mediated low-oxygen response through Ofd1 homologs is well studied in fission yeast, but its overall role in fungal pathogenesis remains ill-defined despite Ofd1 homologs being present in many human-pathogenic fungi (25,66,79).…”
Section: Oxygen and Fungal Disease Progression: Fungal Morphogenesis ...mentioning
confidence: 99%